1992
DOI: 10.1159/000126128
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Regulation of Luteinizing Hormone-Releasing Hormone Release at the Median Eminence Level: Immunocytochemical and Physiological Evidence in Hens

Abstract: Theoretically, the most effective inhibitory control of hypophysiotropic luteinizing hormone-releasing hormone (LHRH) release might occur through a presynaptic inhibition of LHRH neuronal terminals at the median eminence (ME) level. Since: (a) we have recently reported the existence of synaptic contacts between dopamine- and LHRH-containing processes in the ewe ME, and (b) nutritional deprivation induces an ovulatory failure in both birds and mammals, we have assessed the possibility that the anovulatory state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Nevertheless, a direct action of dopamine on LHRH terminals is suggested by the observation of axo-axonic synaptic contacts between dopaminergic and LHRH terminals within the ME (Kuljis & Advis 1989). Such organization is also found in rats (Ajika 1979, Ugrumov et al 1989) and in hens (Contijoch et al 1992). The ability of dopamine to act directly on LHRH neurons could be determined, for instance, by assessing the presence of D2-like receptors on LHRH neurons by immunocytochemistry at the electron microscopic level, or by testing the action of dopamine in vitro on cultured LHRH neurons.…”
Section: Discussionmentioning
confidence: 94%
“…Nevertheless, a direct action of dopamine on LHRH terminals is suggested by the observation of axo-axonic synaptic contacts between dopaminergic and LHRH terminals within the ME (Kuljis & Advis 1989). Such organization is also found in rats (Ajika 1979, Ugrumov et al 1989) and in hens (Contijoch et al 1992). The ability of dopamine to act directly on LHRH neurons could be determined, for instance, by assessing the presence of D2-like receptors on LHRH neurons by immunocytochemistry at the electron microscopic level, or by testing the action of dopamine in vitro on cultured LHRH neurons.…”
Section: Discussionmentioning
confidence: 94%
“…This age-relat ed difference also raises questions about the ability of the neurovascular terminals in middle-aged animals to con centrate and store LHRH for release during the preovula tory LH surge. Regulation of LHRH neurosecretion is probably modulated by a balance of excitatory and inhibi tory influences, and the median eminence is a potentially important site for that modulation [28,29]. Effective inhibitory control [29] might be required to limit constitu tive release of the peptide from terminals in the median eminence and to enable the build-up of LHRH stores.…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of LHRH neurosecretion is probably modulated by a balance of excitatory and inhibi tory influences, and the median eminence is a potentially important site for that modulation [28,29]. Effective inhibitory control [29] might be required to limit constitu tive release of the peptide from terminals in the median eminence and to enable the build-up of LHRH stores. Age-related alterations in neuromodulatory influences on LHRH terminals could therefore result in diminished stores of LHRH available for release in aging females.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, Bergendahl and Veldhuis (1995) mentioned in their review that inadequate nutritional intake impaired LH secretion mainly via GnRH release from hypothalamus. Similarly, in the chicken, it was suggested that starvation suppressed release of GnRH from the median eminence (Contijoch et al, 1992). However, it was suggested in the chicken that pituitary sensitivity to GnRH declined in an early phase of starvation because administration of GnRH had no effect on the plasma LH level in that phase (Tanabe et al, 1981).…”
Section: Dependent Variablementioning
confidence: 99%